2014
DOI: 10.1016/j.redox.2014.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Free radical derivatives formed from cyclooxygenase-catalyzed dihomo-γ-linolenic acid peroxidation can attenuate colon cancer cell growth and enhance 5-fluorouracil׳s cytotoxicity

Abstract: Dihomo-γ-linolenic acid (DGLA) and its downstream fatty acid arachidonic acid (AA) are both nutritionally important ω–6 polyunsaturated fatty acids (ω–6s). Evidence shows that, via COX-mediated peroxidation, DGLA and its metabolites (1-series prostaglandins) are associated with anti-tumor activity, while AA and its metabolites (2-series prostaglandins) could be tightly implicated in various cancer diseases. However, it still remains a mystery why DGLA and AA possess contrasting bioactivities. Our previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
68
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(80 citation statements)
references
References 42 publications
(43 reference statements)
11
68
1
Order By: Relevance
“…Previous studies in the colon cancer cell line HCA-7 showed that direct treatment of 8-HOA as well as accumulated endogenous formation of 8-HOA in D5D knockdown and COX-catalyzed DGLA peroxidation can not only inhibit cell growth, but also enhanced the cytotoxicity of the chemotherapy drug 5-FU, likely via a p53-dependent pathway [36,37]. The current study aimed to extend the supposition that D5D knockdown in conjunction with DGLA treatment can also be used to inhibit growth of pancreatic cancer cells via p53 independent pathway, using pancreatic cancer cell line BxPC-3 which has both high COX-2 expression and mutated p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in the colon cancer cell line HCA-7 showed that direct treatment of 8-HOA as well as accumulated endogenous formation of 8-HOA in D5D knockdown and COX-catalyzed DGLA peroxidation can not only inhibit cell growth, but also enhanced the cytotoxicity of the chemotherapy drug 5-FU, likely via a p53-dependent pathway [36,37]. The current study aimed to extend the supposition that D5D knockdown in conjunction with DGLA treatment can also be used to inhibit growth of pancreatic cancer cells via p53 independent pathway, using pancreatic cancer cell line BxPC-3 which has both high COX-2 expression and mutated p53.…”
Section: Discussionmentioning
confidence: 99%
“…A unique structural moiety in DGLA led to the formation of a novel free radical byproduct, 8-hydroxyoctanoic acid (8-HOA) [35]. More recently, the Qian lab also demonstrated that 8-HOA is the bioactive metabolite responsible for DGLA’s anti-cancer effect [35,36]. Direct treatment with certain level of 8-HOA as well as accumulation of 8-HOA from DGLA-treated cells were also found to be essential to inhibit growth of colon cancer cells (e.g., HCA-7 colony 29, overexpresses COX-2) via arresting the cell cycle in G1 and promoting cell apoptosis in a p53-dependent manner [37].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there have been very limited studies focusing on this topic. Recent research from Qian’s group found that DGLA’s free radical derivatives from lipid peroxidation could inhibit human colon cancer cell growth, [43] while direct treatment with DGLA had no effect on cell proliferation, probably due to effective D5D-catalyzed conversion of DGLA to AA. However, when this conversion was limited by D5D knockdown via siRNA transfection, DGLA treatment led to a significant inhibition in cell growth (unpublished research result from Qian’s group).…”
Section: Implications Of ω-6s In Cancermentioning
confidence: 99%
“…[4043,81,82] The contribution to the study on lipid peroxidation enables us for the first time to investigate the effect of individual ω-6 free radical metabolites and pathways in cancer development. These studies showed that in addition to a C-15 oxygenation shared by both DGLA and AA, there is a unique C-8 oxygenation pathway present during COX-catalyzed DGLA peroxidation, which can give rise to exclusive DGLA free radicals.…”
Section: Mechanisms Of the Anti-cancer Effects Of ω-6 Pufasmentioning
confidence: 99%
See 1 more Smart Citation